THE CONTENT OF INVESTMENT ACTIVITY IN THE CONTEXT OF MACROECONOMIC INSTABILITY - Hassan Ali Al-Ababneh; Firas Wahsheh; Olha Popova; Liubov Vasylyshyna (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The paper considers the main features of investment activity in modern conditions of macroeconomic instability. The prerequisites for the formation of new approaches to the development of investment solutions in the conditions of macroeconomic instability are considered. The essence of macroeconomic instability is determined and conceptual factors of its influence on investment activity are identified. An in-depth analysis of evolutionary-revolutionary models for the development of financial and economic systems is carried out on the basis of which, the author has created an algorithm for the development of these models in modern conditions of macroeconomic instability. It is substantiated that during periods of economic recession and financial and economic crises, the relevance and conceptual need for revising the content of investment activity based on the application of a proactive approach, as a means that allows not only to minimize financial losses, but to prevent them, increases. The key mechanisms of reactive and proactive investment management are considered, their advantages and disadvantages are highlighted, which made it possible to transform them into modern realities, taking into account the maximum time period for a more accurate and reliable analysis.